An Epidemiological study of health behavioral and protective factors among school going adolescents (aged 13-17 years) of Ahmedabad, Gujarat using the Global School-based Student Health Survey (GSHS) questionnaire - Christian, Donald S; Patel, Mansi; Solanki, Asha K (Indian Journal of Community Health, 2020)
Background: Adolescence is considered as the next unsurpassed stage of life to childhood targeting for preventive and health promotional activities. Encouraging these activities firstly requires identification of high-risk behaviors and protective factors prevalent among such adolescents during current epidemiological transition period. Objective: To estimate the prevalence of various health behavioral and protective factors among school going adolescents of Ahmedabad. Methodology: A cross sectional study was conducted among 403 school going adolescents of rural field practice areas of a medical institute using GSHS self-administered questionnaire -Indian version. Almost all aspects of the questionnaire such as dietary behaviors, hygiene, mental health, physical activity, protective factors, tobacco use, violence & unintentional injury, alcohol use and drug use were included in this study. Results: Out of a total of 403 students, 25.3% and 48.9% of students ate fruits and vegetables three or more times a day in past 30 days, respectively. About 41.2 % of students drank carbonated drinks on two or more times per day. Majority (77.7%) of the students brushed their teeth two times per day in past 30 days. Some 9.2% of students felt lonely in past 12 months and 8.4% of students had no close friends. Around 46.2% of students missed classes or school without permission in past 30 days. 30% of students remained physically active for all 7 days in last week. A few of students smoked cigarettes (2.5%) and used any form of tobacco (7.9%) on one or more days during past 30 days. The significant differences were found in many areas of risk behaviors as well as protective factors between boys and girls. Conclusion: Various unhealthy behaviors and protective factors were identified among school going adolescents from the present study. The difference was significant.